Scaling up health service delivery : from pilot innovations to policies and programmes - Simmons, Ruth (Ruth S.); Fajans, Peter; Ghiron, Laura (World Health Organization ; ExpandNet, 2007)
This book addresses some of the issues involved in scaling up health service delivery. The focus is on ways to increase the impact of health service innovations that have been tested in pilot or experimental projects so as to benefit more people and to foster policy and program development on a lasting, sustainable basis. The book addresses a major failure in the global health and development field: namely, the failure to expand the many successful small-scale pilot or demonstration projects that have been organized around the world so as to benefit larger populations than those initially served. It presents a conceptual framework for thinking about scaling up as well as case-studies from Africa, Asia and Latin America where the potential for expansion was a concern from the very inception of pilot or experimental projects. The case-studies discuss family planning and related sexual and reproductive health service interventions as well as other innovations in primary health care.--Publisher's description.